Study of Railway 1:15 Turnout Geometry at Kulai Station (KI08) for Electrified Double Track Project (EDTP) - Ahmad Yazid, Mohammad Lutfi Hakimi; Nagarajoo, Karthigesu (Progress in Engineering Application and Technology, 2024)
This study aimed to study the crucial part in turnout types 1:15 that have been used for Section 4 which in Kulai (KI08) on Electrified Double Track Project (EDTP) from Gemas to Johor Bahru. The primary focus was on assessing the consequences of out tolerance measurement for KI08 that potentially derailment to happen. In fact, it investigated track gauge measurement, balancing of the guard rail and contact between stock rail and switch rail for both straight or main line and curved line. Every investigated part got measurement and tolerance that is very crucial from safety aspects. Out tolerance measurement will lead to narrow or wider track gauge that will cause derailment to happen and the same consequences apply for balancing of guard rail and contact between stock rail and switch rail too. By investigated these part in turnout types 1:15, this paper aimed to provide comprehensive understanding the crucial part in turnout. Last but not least, the findings offered valuable insights into the importance of keep the measurement in turnout is within tolerance since the turnout is used for changing train direction.